Decay of liquid metallic macroparticles in plasma-beam systems due to rayleigh instability - Bizyukov, A.A; Chibisov, A.D.; Romashchenko, E.V.; Kolyada, Yu.E. (Вопросы атомной науки и техники, 2017)
The possibility of decay of liquid macroparticles (MP) in collisionless plasma of vacuum arc source as a result of charging by high-energy electron beam and subsequent development of the Rayleigh instability is studied. The criteria of droplets decay are obtained. It has been estimated the charge time of droplets by electron beam, the time of droplets decay, as well as the heating time to a temperature when the thermionic emission occurs. It was shown that the MP heating time significantly exceeds the development of the Rayleigh instability. Изучена возможность распада жидких макрочастиц (МЧ) в бесстолкновительной плазме вакуумного дугового источника плазмы в результате их зарядки электронным пучком высоких энергий и последующим развитием неустойчивости Рэлея. Получены критерии распада МЧ, время зарядки МЧ электронным пучком, время распада МЧ, а также время нагревания до температуры, когда происходит разрядка МЧ термоэмиссионным током. Показано, что время разогрева МЧ значительно превышает время развития неустойчивости Рэлея. Вивчено можливість розпаду рідких макрочасток (МЧ) у плазмі без зіткнень, яка створюється вакуумно-дуговим джерелом плазми, в результаті їх зарядки електронним пучком високих енергій і подальшим розвитком нестійкості Релея. Отримано критерії розпаду МЧ, час зарядки МЧ електронним пучком, час розпаду МЧ, а також час нагрівання до температури, коли відбувається розрядка МЧ термоемісійним струмом. Показано, що час розігріву МЧ значно перевищує час розвитку нестійкості Релея.